'Brazilians'1 houses': an example of nostalgia and a proposal of touristic empowerment. (July 2016) - Neto, Alda H
On the second half of the 19th century, Portuguese emigration to Brazil was a major historical and sociological phenomenon. After an arduous path, the Portuguese returned and became part of the political, economical, social and artistic lives of their hometowns, causing a change on the architectural landscape in the north of the country. These emigrants built houses that became hugely important as social buildings; they represented the way in which each one of them inserted himself in the community that saw him leave. The taste printed by each one of the emigrants in their houses made them a landmark for the application of several artistic movements of that time in the country as well as in Europe, such as Art Noveau (wrought iron) or Romanticism (gardens). The exterior and the interior of these houses portray a constant connection to Brazil and Portugal, proved by the national flags that hang on the façades or by the landscapes represented in paintings or tile panels. However, many of those houses were already destroyed and along them the memory of a Brazilian that stated himself as the paradigm of the self-made man. This type of houses was an important example of the emigration architecture, main feature of the Iberian Peninsula, which needs a fast cultural and touristic valuation, once it was part of a people's material memory. To protect this kind of patrimony and avoid a loss of a vast estate about emigration, it is considered that these houses may be grouped into a set of touristic routes that will lead us to the finding and knowledge of the material and immaterial inheritance of these men and women. Setting up these routes might constitute an important step towards the museualization of the migrations, recovering the cultural routes of the migrant people.